PERBEDAAN EMPATI DAN REGULASI EMOSI DALAM PERILAKU BULLYING ANTARA MAHASISWA LAKI-LAKI DAN PEREMPUAN YANG MENGIKUTI UKM - Shafira Erviana; Latifah Nur Ahyani (Jurnal Psikohumanika, 2017)
This study aims to empirically examine the differences in empathy and emotional regulation in bullying behavior among male and female college students following UKM. Subjects in the study in this study were male and female students who participated in UKMMenwa, Mapala, Sekam, and Racana involving 80 students. In this study using purposive sampling techniques and tools used to obtain data is the scale of empathy and the scale of emotional regulation. The result of data analysis with SPSS 15.0 for Windows program obtained the test coefficient of t- (test) on empathy and regulation of male emotion with mean value 124,28 female equal to 113,65 and known coefficient correlation value of emotional regulation and empathy in man Male and female with a coefficient of 0.060 (p> 0.05) indicating no difference in empathy and emotional regulation in bullying behavior between male and female students following UKM. The result of the analysis of difference of male and female empathy is known t men equal to 45,345 and t female equal to 46,816 with value with p value 0.000 (p <0,01) this indicate there is difference of empathy to bullying behavior significant between men and Women, women have the ability to empathize more than men. The result of the analysis of male and female emotional regulation was found t men value of 56,188 and female t value equal to 44,159 with p value 0.000 (p <0,01) this shows there is difference of emotion regulation to bullying behavior that significant between men Men and women who follow UKM